Loss of PIKfyve drives the spongiform degeneration in prion diseases. Issue 9 (22nd July 2021) - Lakkaraju, Asvin K K; Frontzek, Karl; Lemes, Emina; Herrmann, Uli; Losa, Marco; Marpakwar, Rajlakshmi; Aguzzi, Adriano
Abstract: Brain‐matter vacuolation is a defining trait of all prion diseases, yet its cause is unknown. Here, we report that prion infection and prion‐mimetic antibodies deplete the phosphoinositide kinase PIKfyve—which controls endolysosomal maturation—from mouse brains, cultured cells, organotypic brain slices, and brains of Creutzfeldt‐Jakob disease victims. We found that PIKfyve is acylated by the acyltransferases zDHHC9 and zDHHC21, whose juxtavesicular topology is disturbed by prion infection, resulting in PIKfyve deacylation and rapid degradation, as well as endolysosomal hypertrophy and activation of TFEB‐dependent lysosomal enzymes. A protracted unfolded protein response (UPR), typical of prion diseases, also induced PIKfyve deacylation and degradation. Conversely, UPR antagonists restored PIKfyve levels in prion‐infected cells. Overexpression of zDHHC9 and zDHHC21, administration of the antiprion polythiophene LIN5044, or supplementation with the PIKfyve reaction product PI(3, 5)P2 suppressed prion‐induced vacuolation and restored lysosomal homeostasis. Thus, PIKfyve emerges as a central mediator of vacuolation and neurotoxicity in prion diseases. Synopsis: The phosphoinositide kinase PIKfyve is identified as the driver of brain vacuolation (spongiosis) in prion diseases. A hierarchy of events, starting the delocalization of PIKfyve‐specific acyltransferases and culminating in the enlargement of endolysosomes underlying spongiosis, is established. The kinase PIKfyve converts phosphoinositol‐3‐phosphate into PI(3, 5)‐diphosphate. PIKfyve is physiologically acylated by the acyltransferases zDHHC9 and zDHHC21. Prion infection induces PIKfyve deacylation, thereby reducing its half‐life and depleting it from infected cells. PIKfyve depletion results in spongiosis and lysosomal defects. Prion‐induced spongiosis can be rescued by PI(3, 5) analogues or by overexpressing zDHHC9/21. Abstract : The phosphoinositide kinase PIKfyve is identified as the driver of brain vacuolation (spongiosis) in prion diseases. A hierarchy of events, starting the delocalization of PIKfyve‐specific acyltransferases and culminating in the enlargement of endolysosomes underlying spongiosis, is established.